2013
DOI: 10.12735/jbm.v2i3p12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corporate Governance on Non-Performing Loans of Nigerian Deposit Money Banks

Abstract: This study examines the impact of Corporate Governance (CG) variables of Board Size

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
2
4
0
1
Order By: Relevance
“…The addition or reduction in the number of directors in the board size does not significantly affect the banks' non-performing loans. This finding is consistent with the finding of Nyor et al (2013). However, it is inconsistent with the finding of Ahmad et al (2016).…”
Section: Regression Results and Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The addition or reduction in the number of directors in the board size does not significantly affect the banks' non-performing loans. This finding is consistent with the finding of Nyor et al (2013). However, it is inconsistent with the finding of Ahmad et al (2016).…”
Section: Regression Results and Discussionsupporting
confidence: 60%
“…Conversely, Nyor et al (2013) found that corporate governance did not significantly impact the non-performing loan. Based on the previous studies conducted, only a limited number of research studies studied the impact of corporate governance variables on the non-performing loan in Indonesia.…”
Section: Previous Empirical Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…Rinaningsih, 2008;Hariani, 2011;Poudel dan Hovey, 2012;Bourakba dan Zerargui, 2015;Ahmad et al, 2016. Peneliti lain menemukantidak menemukan pengaruh signifikan corporate governance terhadap resiko kredit, Nyor dan Mejabi (2013) Mendasarkan pada temuan penelitian yang beragam di atas dan saran penelitian Ramli et al (2014), penulis tertarik untuk menginvestigasi kembali pengaruh karakteristik perusahaan terhadap shari'ah governance dan dampaknya pada resiko kredit (pembiayaan).…”
unclassified